2016
DOI: 10.3892/etm.2016.3531
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen therapy increases BDNF expression and improves post-stroke depression in ovariectomy-treated rats

Abstract: Abstract. The present study investigated the effect of exogenous estrogen on post-stroke depression. Rats were exposed to chronic mild stress following middle cerebral artery occlusion. The occurrence of post-stroke depression was evaluated according to the changes in preference for sucrose and performance in a forced swimming test. Estrogen therapy significantly improved these neurological symptoms, indicating that estrogen is effective in treating post-stroke depression. Increased brain-derived neurotrophic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…The menopausal period—a very specific state for women—is produced by the decreased secretion of the female gonadal hormones by the ovaries [1,2,3]. Numerous data of preclinical and clinical studies have shown that estrogen deficiency during menopause increases the susceptibility to mood disturbances, including depression [4,5,6,7]. On the other hand, the menopausal state in ovariectomized (OVX) female rodents and menopausal women is also characterized by vitamin D (VD) deficiency or insufficiency [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The menopausal period—a very specific state for women—is produced by the decreased secretion of the female gonadal hormones by the ovaries [1,2,3]. Numerous data of preclinical and clinical studies have shown that estrogen deficiency during menopause increases the susceptibility to mood disturbances, including depression [4,5,6,7]. On the other hand, the menopausal state in ovariectomized (OVX) female rodents and menopausal women is also characterized by vitamin D (VD) deficiency or insufficiency [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…BDNF is known to be a neurotrophic protective factor, involved in the regulation of several critical neuronal functions and neuroplasticity in patients who suffer nervous system diseases such as Parkinson’s disease, Alzheimer’s disease, and stroke [35,36,37]. Several empirical studies have indicated the benefits of the increased expression of BDNF or receptor in different stages of stroke such as acute ischemic stroke, the rehabilitation process, and recurrence [37,38,39,40]. The expression of BDNF has been demonstrated to have benefits on stroke recovery through several mechanisms and proposed actions including the increase in brain repair [7], the acceleration of neurogenesis [41], and the promotion of angiogenesis [42].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, interconnections between the hypothalamic-pituitary-ovarian (HPO) and HPT axes have been reported; notably hypothyroidism is closely associated with hyperprolactinemia, as well as menstrual problems, including oligomenorrhea, amenorrhoea and polymenorrhea ( 50 ). Therefore, an imbalance of hormones acting at the HPT and HPO axes may have adverse effects on mental, thyroid and/or uterine health ( 51 ).…”
Section: Discussionmentioning
confidence: 99%